A method for determining tool group flexibility with uncertain machine availability - applications in a semiconductor manufacturing process / Adam Terry, Mamidala Ramulu and Posinasetti Nageswara Rao - Terry, Adam; Ramulu, Mamidala; Nageswara Rao, Posinasetti (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2009)
The production of Integrated Circuits (IC) is a detailed and exacting process requiring tight specifications and precise equipment. The high cost and unique traits of this equipment requires high utilization and maximum throughput to achieve real profits. The design of fabrication facility (FAB) processes requires a thorough understanding of the adverse effects that random machine availability has on system performance. These effects (increased cycle time, decreased and variable throughput, etc) can be offset by tool group flexibility. Tool group flexibility can be described by two measures: machine flexibility (the number of tasks a machine can perform) and task flexibility (the number of machines qualified to perform a specific task). These two measures are related by the ratio of the number of machines in the tool group to the number of tasks that the group must perform. This paper utilizes a combined linear programming and simulation approach in an attempt to model the manufacturing system to gain insight into the production dynamics. The model is based on current production methodology and the use of modular equipment (steppers). The results include some insight into the added cost of flexibility and the associated production ramifications.